2014
DOI: 10.1002/ceat.201400462
|View full text |Cite
|
Sign up to set email alerts
|

Influence of NaCl on Granulometric Characteristics and Polymorphism in Batch‐Cooling Crystallization of Glycine

Abstract: The effect of NaCl added in different quantities on thermodynamic properties, granulometric characteristics, and structure of glycine in a crystallization process was investigated. Solubilities of α‐ and γ‐polymorphs in the presence of varying amounts of NaCl were analyzed. In order to examine the impact of the additive on granulometric properties of glycine, crystal morphology was examined by observing crystals under a scanning electron microscope. Crystal size distribution was determined by sieve analysis. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The PXRD patterns for α-form and γ-form crystals differed due to the different molecular arrangements in their crystalline structures. The α-form structure was identified by characteristic peaks at 2θ of ~19.05 • , ~29.9 • , and ~35.4 • , and the γ-form structure was identified by characteristic peaks at 2θ of ~21.8 • , ~25.3 • , and ~39.1 • [30,32]. Here, all the PXRD patterns were obtained with a slow scan rate of 0.02 • /s, and no characteristic peaks of β-form were observed at ~18.0 • or ~24.8 • , which also confirmed that there was no β-form in the samples [30,32,33].…”
Section: Resultsmentioning
confidence: 99%
“…The PXRD patterns for α-form and γ-form crystals differed due to the different molecular arrangements in their crystalline structures. The α-form structure was identified by characteristic peaks at 2θ of ~19.05 • , ~29.9 • , and ~35.4 • , and the γ-form structure was identified by characteristic peaks at 2θ of ~21.8 • , ~25.3 • , and ~39.1 • [30,32]. Here, all the PXRD patterns were obtained with a slow scan rate of 0.02 • /s, and no characteristic peaks of β-form were observed at ~18.0 • or ~24.8 • , which also confirmed that there was no β-form in the samples [30,32,33].…”
Section: Resultsmentioning
confidence: 99%
“…Crystallization is a separation process utilized in the chemical, food, and pharmaceutical industries to purify or produce a new solid phase from a solution, suspension, or melt [1]. Various factors, such as temperature, agitation, saturation, supersaturation, or the presence of additives, can influence the implementation and outcome of the crystallization process by impacting the crystal growth, morphology, and internal structure of obtained crystals [2]. Crystalline form, size, and shape directly affect the physical and chemical properties of solids such as solubility and dissolution rate, as well as downstream processes such as filtration, milling, drying, or tableting; therefore, it is important to have control over the crystallization process.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of acidity on solubility is also very obvious, for example, S. Mishra et al found that the solubility of triisoamyl phosphate first decreased and then increased with the increase of acidity [8]. Crystallization is a key step in the separation and purification, and the factors that affect crystallization are often the influence of temperature, supersaturation, stirring rate, and additives, adding additives to the solution will cause a change in the solubility of the crystalline components, which mainly depends on the role of foreign ions and pH value [9]. GAH plays an important role in the human body [10].…”
Section: Introductionmentioning
confidence: 99%